A Translation Analysis Of English Modal Verbs In Zara Zettira Zr Novel Every Silence Has A Story Into Indonesian Cerita Dalam Keheningan By Ronaldo - PALUPI, FITRI AYU (2012)
This research aims at classifying the variation of translation English modal verbs, getting the dominant of English modal verbs and describing the meaning of English modal verbs in Every Silence Has a Story novel. This theory applies descriptive qualitative research. The data of this research are Indonesian-English sentences containing English modal verbs and its translation. The source of data is Every Silence Has a Story novel and its translation. The data are analyzed by using comparison method. The results of the research show that 1) there are 4 variations of translation English modal verbs: English modal verb is translated into adverb, English modal verb is translated into verb, English modal verb is translated into adjective, and English modal verb is not translated or deleted; 2) the dominant translation variation of English modal verb is English modal verb is translated into Indonesian adverb; 3) there are 8 meanings of English modal verb: ability meaning, futurity meaning, willingness meaning, obligation meaning, prediction meaning, permission meaning, certainly meaning, and possibility meaning.